Cytogenetic aberrations in primary cell cultures of the ovarian surface epithelium. - Chuaire Noack, Lilian; Rondón Lagos, Sandra; Ramírez Corredor, Amparo; Ibáñez Pinilla, Milcíades; Ramírez Clavijo, Sandra (Investigación Clínica, 2013)
Â Our objective was to determine the presence of chromosomal abnormalities in primary cultures of ovarian surface epithelial cells in women of different ages with no history of cancer. Throughout conventional cytogenetic techniques, we analyzed chromosome spreads of cultured ovarian epithelial cells from 10 donors who were 50 or more years old (B) and 16 controls between 20 and 49 years old (A), belonging to the mestizo population in Bogota DC, Colombia. Of the 26 cultures that were analyzed in passage 1, 61.5% had an abnormal chromosome complement (62.5% in A, and 60% in B). Abnormalities included polyploidies, endoduplications and monosomies. Deletions in chromosomes 3 and 11 were found in just one metaphase. None of the samples showed weaknesses or breakpoints. After transforming and applying the exact student”™s t-test for variance heterogeneity, we found significant differences in the frequency of metaphases, that were higher in A than in B (p=0.05), and in the frequency of polyploidies, which were higher in B than in A (p=0.044). Through the application of the Mann-Whitney test, we determined that the frequency of endoduplications was higher in A than in B (p=0.126), without reaching significant differences. There were no significant differences in the frequency of monosomies. The level of significance was set at p â‰¤ 0.05. Taking into account that polyploidization is a marker of chromosomal instability and that the risk of cancer arising from the ovarian surface epithelium augments substantially after menopause, the increase in the frequency of age-associated polyploidies could be used as a predictor of ovarian cancer in women from an ethnically homogeneous population as the mestizo one in Bogota DC.